2011
DOI: 10.1121/1.3583546
|View full text |Cite
|
Sign up to set email alerts
|

A spiral wave front beacon for underwater navigation: Basic concept and modeling

Abstract: A spiral wave front source produces an acoustic field that has a phase that is proportional to the azimuthal angle about the source. The concept of a spiral wave front beacon is developed by combining this source with a reference source that has a phase that is constant with the angle. The phase difference between these sources contains information about the receiver's azimuthal angle relative to the beacon and can be used for underwater navigation. To produce the spiral wave front, two sources are considered:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 11 publications
0
16
0
Order By: Relevance
“…In the first demonstration, we carve a spiral pattern on the metasurface for producing high‐quality acoustic vortex, which has been paid intense attentions recently for diverse applications including microparticle manipulation and acoustic communication . Figure a schematically presents that a vortex beam with the helical wavefront can be created when an incident plane wave is modulated by a Fermat spiral mask.…”
Section: Resultsmentioning
confidence: 99%
“…In the first demonstration, we carve a spiral pattern on the metasurface for producing high‐quality acoustic vortex, which has been paid intense attentions recently for diverse applications including microparticle manipulation and acoustic communication . Figure a schematically presents that a vortex beam with the helical wavefront can be created when an incident plane wave is modulated by a Fermat spiral mask.…”
Section: Resultsmentioning
confidence: 99%
“…Transducers producing first order spiral fields have been recently developed for use in underwater bearing estimation. [7][8][9] This idea is extended to the general case and it is shown that for a given position in space, each spiral wave front appears to come from a different source position. Hence, for free-field reproduction within a circular array of higher order sources each Nth order speaker is similar in performance to an array of 2N þ 1 point sources, a) Author to whom correspondence should be addressed.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] The spiral source transmits a pulse whose phase is a function of the azimuthal angle relative to the source while the reference source transmits a pulse whose phase is constant with angle. By comparing the phases of the two pulses, the vehicle can determine the direction to the beacon.…”
Section: Introductionmentioning
confidence: 99%
“…These sources use two different methods to produce the spiral wave front. 2 The first, the "physical-spiral" transducer, uses a single, active element formed around a spiral backing. The second design, the "phased-spiral" array, uses an array of elements each driven with the appropriate phase to produce the spiral wave front.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation